Immunohistochemical subtypes and their relationship with the clinicopathological and histological aspects of breast cancer - Lourdes González-Longoria Boada; Secundino González Pardo; Francisco López Muñoz (Medisur, 2022)
Background: The prognosis and therapy of breast cancer (BC) is closely related to the histopathological characteristics of the patient. These allow to establish prognostic groups, as support in the decision of effective individual treatments. However, the existing information is limited on the relationship between these aspects and the immunohistochemical subtypes (IHC) of breast cancer in Latin American countries.   Objective: To determine the relationship between the clinical-pathological and histological characteristics with the IHC subtypes of BC in Ecuadorian patients. Methods: An observational of the cross-sectional study was carried out in Ecuadorian patients treated at the Abel Gilbert Pontón Hospital between January 2014 and December 2017. 199 patients with a histopathological diagnosis of BC were included. Clinicopathological variables were analyzed: age, tumor size and lymph node status; histological: type and histological grade. Results: The mean age of the patients was 56,77 ± 11,96 years. Lymph node metastases were observed in most cases (63,3%). The mean tumor size was 3,88 ± 1,61 cm. More than half of the cases (56,8%) presented a moderately differentiated histological grade. The predominant molecular subtype was Luminal A neoplasia (53,8%). The analysis showed a significant association (p <0, 0001) between IHC subtypes and the clinicopathological and histological characteristics of BC. Conclusions: Breast neoplasia in Ecuadorian patients is diagnosed in advanced stages. The study emphasizes the need to introduce IHC receptor tests into clinical practice to help determine the biology of breast cancer, improve the effect on therapy and the patient's prognosis.